Candida albicans Mycofilms Support Staphylococcus aureus Colonization and Enhances Miconazole Resistance in Dual-Species Interactions - Kean, Ryan; Rajendran, Ranjith; Haggarty, Jennifer; Townsend, Eleanor M.; Short, Bryn; Burgess, Karl E.; Lang, Sue; Millington, Owain; Mackay, William G.; Williams, Craig; Ramage, Gordon (Frontiers in Microbiology, 2017)
Polymicrobial inter-kingdom biofilm infections represent a clinical management conundrum. The presence of co-isolation of bacteria and fungi complicates the ability to routinely administer single antimicrobial regimens, and synergy between the microorganisms influences infection severity. We therefore investigated the nosocomial pathogens Staphylococcus aureus and Candida albicans with respect to antimicrobial intervention. We characterized the interaction using biofilm assays and evaluated the effect of miconazole treatment using in vitro and in vivo assays. Finally, we assessed the impact of biofilm extracellular matrix (ECM) on these interactions. Data indicated that the C. albicans mycofilms supported adhesion and colonization by S. aureus through close interactions with hyphal elements, significantly increasing S. aureus biofilm formation throughout biofilm maturation. Miconazole sensitivity was shown to be reduced in both mono- and dual-species biofilms compared to planktonic cells. Within a three-dimensional biofilm model sensitivity was also hindered. Galleria mellonella survival analysis showed both enhanced pathogenicity of the dual-species infection, which was concomitantly desensitized to miconazole treatment. Analysis of the ECM revealed the importance of extracellular DNA, which supported the adhesion of S. aureus and the development of the dual-species biofilm structures. Collectively, these data highlight the clinical importance of dual-species inter-kingdom biofilm infections, though also provides translational opportunities to manage them more effectively.